Role Of Education Program Kindergarten Children In Developing Creative Group B TK Aisyiah Bustanul RA XIII Pengawu - Munirah, Munirah (Bungamputi, 2014)
ABSTRACT The main problem in this study is what forms the creativity of children, How the implementation of educational programs, and educational programs there any role of kindergarten children to develop creativity in group B TK Aisyiah Bustanul Athfal Pengawu XIII? This study aims to determine the form of the development of creativity of children, knowing the implementation of the education program, and determine the role of education programs in kindergarten children to develop creativity in group B TK Aisyiah Bustanul Athfal Pengawu XIII. Data were collected through observation, interviews, and documentation in the descriptive analysis. Based on the results of observations made, it can be concluded that the development of creativity of children in group B TK Aisyiah Bustanul XIII Pengawu RA has increased every week, it is evident from the increasing number of the percentage of children who enter the category is growing ( SB ). In the course of making various forms of platisin, the development of creativity of children increased from 8.00 % to 25.00 %. In the course of making various shapes of blocks, development of creativity of children increased from 12.00 % to 24.00 %. In the course of making various shapes of beads, the development of creativity of children increased from 20.00 % to 40.00 %. And in the drawing, the development of creativity of children increased from 16.00 % to 36.00 % and in coloring activities, the development of creativity of children increased from 24.00 % to 40.00 %, as well as in paper folding activities, the development of creativity of children increases from 25.00 % to 36.00 %. Implementation of educational programs in group B TK Aisyiah Bustanul XIII Pengawu RA according to the existing curriculum, and in accordance with the indicators through the annual program , the semester program, the program weekly and daily programs. The role of education programs in kindergarten expands creativity kindergarten children in group B Aisyiah Bustanul Athfal XIII Pengawu always there, play a role to make children can create on of not being able to because the program was instrumental in developing a childs creativity and without any meaningful development programs and creativity children will not be able to thrive. Keywords : Education Program Kindergarten, Child Creativity